Pendidikan Karakter Dalam Perspektif Profetik Pada Puisi-Puisi Abdul Wachid B.S. - Mahroso Doloh (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This study aims to examine and describe prophetic values in the poems of Abdul Wachid B.S. as something that can drive the success of character education in a prophetic perspective. The approach used in this research is Riffaterre semiotic approach with qualitative descriptive analysis method. The results of the study were found as follows. There are values or matters related to the three prophetic pillars: first, the humanization pillars are as follows: (1) calling for brotherhood, (2) solidarity on the basis of humanity, and (3) noble values maintained in the face of rapid technological developments. Second, the pillars of liberation contain the following: (1) sympathy by voicing the voice of liberation for the workers, (2) the effort to improve human dignity, and (3) there is an element of unwillingness against injustice prevailing on this earth. Third, the transcendental pillars that vocalize some matters relating to transcendence are: (1) establishing a servant's trust in God, (2) awakening the weakness of man, so that he must always be dependent on God, and (3) should always remind God in any circumstance. From some of the things that appear on the prophetic pillars it is an education that educates the nation's children (the readers) to achieve a prophetic character or it can be said an education that encourages the success of character education (especially character education in the prophetic perspective).